Case Report : Hepatic Cirrhosis and Nephrolithiasis - Risnandar Risnandar; Yoga Rizki Danil; Yuharika Pratiwi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Liver cirrhosis and nephrolithiasis are significant health problems with different pathophysiological mechanisms. Liver cirrhosis, the final stage of chronic liver disease, is characterized by fibrosis and regenerative nodules, leading to severe complications, including portal hypertension and liver failure. Nephrolithiasis, commonly known as kidney stones, is a common urological condition characterized by the formation of stones in the renal system. Although these conditions are distinct, metabolic and physiological changes in cirrhotic patients may predispose to nephrolithiasis. It was reported that a man came to the emergency room of RSUD Dr. Suhatman MARS with complaints of left-sided low back pain that had been felt for 1 week. The complaint was accompanied by shortness of breath which was getting worse over time. The patient also felt cough, headache, nausea, fatigue, urine slightly coloured like tea, weight loss. The patient has a history of untreated kidney stones. The patient has a history of hepatitis 31 years ago. The main objective of investigating the coexistence of liver cirrhosis and nephrolithiasis is to understand the relationship between these two conditions and to develop effective management strategies that can address their combined impact on patients.